A usinabilidade do aço inoxidável austenítico ABNT 304 - Lourenço, Carlos José (1996)
Austenitic stainless steels are chiefly used in the chemical and food industries mainly because of their excellent strength and corrosion resistance. They are, however, considered difficult to machine materials due to their high ability to workharden and large chip-tool contact length produced, which generate high cutting forces and elevated temperatures, promoting high tool wear rates.The present work compares the machinability of two AISI 304 austenitic stainless steels where one o f them has suffered small alterations on its chemical composition (within the range allowed in its specification) and manufacturing process with the aim o f improving its machinability (modified AISI 304 stainless steel - 304M).Tool life tests on both work material were carried out when surface milling using a six tooth milling cutter and triple coated cemented carbide inserts (ISO P45). A program which optimises the number of tests required to give the expanded Taylor’s equation coefficients with a high level o f reliability (developed by other members o f the machining research laboratory - LPU / UFU) was used. During the tool life tests power consumption and surface roughness (Ra parameter) were monitored and swarf was colected at the beginning, middle and end o f each test for analysis. Chip-tool interface temperature (toolchip thermocouple method) was studied on both work materials when turning with uncoated cemented carbide tools (ISO K10) In general a superior machinability was presented by the modified 304M steel in terms of tool life, power consumption and chiptool interface temperature. Surface roughness and chip caracteristics showed no conclusive results.